PENGETAHUAN TENTANG SADARI PADA PASIEN KANKER PAYUDARA (CAMAMMAE) DI RUMAH SAKIT UMUM PUSAT SANGLAH DAN RUMAH SAKITPRIMA MEDIKA BALI NOVEMBER 2012 - Sindhu Nugraha; Tjakra Wibawa Manuaba (Intisari Sains Medis, 2015)
One of theearly inspectionto determinebreastcanceris sadari (periksa payudara sendiri). By doing sadari,patients will beable to knowifthere is alumporsomething that isabnormal. Sadarican be donealoneafter showerby standing infront of the mirror. Researchconducted in2 hospitalsin Denpasartogeta description of thepatient's knowledgeaboutbreastcancer.Resultsin gettingfrom 30breast cancer sampleswere4 patients(13.3%) breast cancer knowaboutsadari. Thenfrom 4breastcancerpatientsknowaboutsadari, 2 patients(50%) didsadari.The remainingsample of26 patients(86.7%) did not know aboutsadari. They got information aboutsadarifromfamily orfriends who'vehad breast cancer. Patientswho foundabnormalities from the examinationare usually notcameto the hospital, butthey didn’t care about it,socomein a bad state.